2022
DOI: 10.3390/ijms232012678
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Amyloid-β (1-42) Peptide Inhibits the Store-Operated Calcium Entry in HT-22 Cells

Abstract: Dysregulation in calcium signaling pathways plays a major role in the initiation of Alzheimer’s disease (AD) pathogenesis. Accumulative experimental evidence obtained with cellular and animal models, as well as with AD brain samples, points out the high cytotoxicity of soluble small oligomeric forms of amyloid-β peptides (Aβ) in AD. In recent works, we have proposed that Aβ-calmodulin (CaM) complexation may play a major role in neuronal Ca2+ signaling, mediated by CaM-binding proteins (CaMBPs). STIM1, a recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 82 publications
4
36
0
Order By: Relevance
“…Moreover, several ER proteins have been shown to be involved in Aβ(1–42) production, and also in the Aβ(1–42) dysregulation of intracellular calcium, reviewed in [ 21 ]. In a recent work, we reported that nanomolar concentrations of the Aβ(1–42) peptide can inhibit SOCE [ 30 ]. Therefore, we experimentally measured the SOCE response in U251 astrocytes treated with cytokines and in untreated Control U251 astrocytes ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several ER proteins have been shown to be involved in Aβ(1–42) production, and also in the Aβ(1–42) dysregulation of intracellular calcium, reviewed in [ 21 ]. In a recent work, we reported that nanomolar concentrations of the Aβ(1–42) peptide can inhibit SOCE [ 30 ]. Therefore, we experimentally measured the SOCE response in U251 astrocytes treated with cytokines and in untreated Control U251 astrocytes ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we found that the treatment of U251 cells with the cytokines TNF-α (30 ng/mL), IL-1α (3 ng/mL) and C1q (400 ng/mL) for 24 h produced a large depletion of ER calcium content, and also a large attenuation of SOCE. The latter result can be seen as a direct effect of Aβ(1–42) generation in these A1-like astrocytes, because we previously demonstrated that only nanomolar concentrations of intracellular Aβ(1–42) are needed to inhibit SOCE activity [ 30 ]. In addition, the enhanced release of calcium from the ER can generate a feed-forward cycle, leading to potentiation of the production of neurotoxic Aβ peptides in A1-like reactive astrocytes, since it has been demonstrated that Aβ-induced BACE1 upregulation can be blocked by preventing calcium influx through treatment with 2-aminoethoxydiphenyl borate, an inhibitor of inositol trisphosphate-dependent calcium release from the ER, and U73122, an inhibitor of phospholipase C [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of calcium homeostasis observed in Alzheimer’s disease was attributed to the inhibition of LTCC by CaM–Aβ complexes. In a subsequent study, using the same fluorescence-labeled Aβ and Alexa488-labeled secondary antibodies for primary anti-PDI and anti-CaM or stromal interaction molecule 1 (STIM1) labeled with green fluorescent protein (STIM1-GFP), Gutiérrez-Merino and colleagues demonstrated that prior to the internal dysregulation of calcium homeostasis, a perturbation of store-operated calcium entry occurs through the internalization of Aβ and its inhibition of STIM1, along with partial activation of the ER Ca 2+ -leak channels [ 102 ]. For these measurements, variations in donor fluorescence were analyzed, and the R 0 and the spectral overlap integral (J) values were obtained for the Aβ*555–SPM1-GFP donor–acceptor pair [ 102 ].…”
Section: Gutiérrez-merino’s Use Of Fret In Imaging Studies Of Biologi...mentioning
confidence: 99%
“…Particularly relevant among intracellular targets of Aβ(1–42) oligomers are neuronal non-amyloidogenic proteins showing high affinity for nanomolar concentrations of Aβ peptides, because critical concentration values in the sub micromolar range have been reported for the induction of Aβ(1–42) fibrillization [ 37 , 38 ], and concentrations of non-fibrillar Aβ peptides within the nanomolar range have been reported in the brain [ 39 , 40 , 41 ]. Among these proteins, the dissociation constant of Aβ(1–42) has been reported to be around 1 nM only for tau [ 42 ], cellular prion protein (PrP C ) [ 43 ], glycogen synthase kinase 3α (GSK3α) [ 44 ], calmodulin (CaM) [ 45 ], and likely stromal interaction molecule 1 (STIM1) [ 46 ]. Human PrP C is a glycoprotein that largely localizes to cholesterol-rich lipid rafts on the outer surface of the cell membrane, thereby acting as a high-affinity receptor for extracellular Aβ oligomers in concert with the low-density lipoprotein receptor-related protein-1 [ 47 ].…”
Section: Introductionmentioning
confidence: 99%